SOAP2: an improved ultrafast tool for short read alignment - Li, Ruiqiang; Yu, Chang; Li, Yingrui; Lam, Tak-Wah; Yiu, Siu-Ming; Kristiansen, Karsten; Wang, Jun (Bioinformatics, 2009)
SOAP2 is a significantly improved version of the short oligonucleotide alignment program that both reduces computer memory usage and increases alignment speed at an unprecedented rate. We used a Burrows Wheeler Transformation (BWT) compression index to substitute the seed strategy for indexing the reference sequence in the main memory. We tested it on the whole human genome and found that this new algorithm reduced memory usage from 14.7 to 5.4 GB and improved alignment speed by 20–30 times. SOAP2 is compatible with both single- and paired-end reads. Additionally, this tool now supports multiple text and compressed file formats. A consensus builder has also been developed for consensus assembly and SNP detection from alignment of short reads on a reference genome. Availability: http://soap.genomics.org.cn Contact: soap@genomics.org.cn